Effects of in ovo injection of organic selenium on the hatchability of broiler breeder hen eggs and resulting chick physiology and performance - Farhad Ghane‐Khoshkebijari; Alireza Seidavi; Mehrdad Bouyeh (Veterinary Medicine and Science, 2024)
Abstract Background Selenium is an essential mineral for poultry. The conflicting reports about its in ovo injection are the justification for the more detailed investigation. Objectives The aim of this study was to investigate the effects of in ovo injection of organic selenium on the hatching traits of broiler chickens and their performance. Methods Three hundred and twenty eggs of Ross 308 strain with an average weight of 65 g and 160 chicks were randomly divided into 4 treatment groups (each with 8 replicates of 10 eggs each for hatching parameters and 4 replicates of 10 chicks for broiler farming parameters): negative control (no injection), positive control (in ovo injection of 0.272 mL of normal saline solution) and 2 selenium treatments (in ovo injection of 2.72 or 5.44 μg of organic selenium). Injection was into the amniotic sac on the 10th day of incubation. Effects of in ovo injection on hatching and performance traits, blood parameters, immune responses, carcass characteristics, meat fatty acid profile, cecal microbial population and selenium consternation in the tibia were measured. Results Fewer chicks from the injected treatments hatched than from the negative control group (p < 0.01). However, the injection of selenium increased feed intake and the final weight of the birds (p < 0.01). Blood parameters were also affected. Glucose and cholesterol in experimental treatment chicks was lower than those of the controls (p < 0.01), whereas blood lipoproteins (VLDL, LDL and HDL) and the ratio of cholesterol to HDL was significantly increased in the treatments injected with selenium (p < 0.01). There was no significant difference in the immune response or microbial population between the experimental groups, but carcass components, such as thigh, breast, wing and abdominal fat weight, were significantly greater in the selenium treatments. Conclusions Intra‐egg injection of organic selenium produced favourable effects on performance of broiler chickens, although it had no effect on immune response or microbial population. However, the negative effect on hatching of chickens needs to be prevented to result in an acceptable economic return for the producer.